The Politics Of China’s Global Peace-Making: Initiating Stability for Long Term Economic Expansion - Gozali, Gufron; Al-Fadhat, Muhammad Faris (Faculty of Social and Political Sciences, Universitas Diponegoro, 2024)
China’s role in global peace-making initiatives raises critical questions about the underlying objectives of these efforts. Some scholars interpret this as an attempt by China to extend its political influence and pursue hegemonic ambitions globally. Others view it as China’s strategy to fill the power vacuum left by the United States. However, the primary goal of China’s initiatives appears to be achieving stability, which is essential for realizing its vision of becoming a prosperous nation by 2049. This article explores the key motivations driving China’s active participation in global peace-making. Utilizing qualitative methods, with an emphasis on in-depth literature reviews, the study draws on two types of data sources. The first is primary data from official statements, including speeches and documents, while the second comprises secondary data from academic journals, scholarly articles, think tank reports, and mass media. The article argues that China’s peace efforts align with its long-term economic expansion interests and asserts that China’s substantial global investments are aimed at fostering both peace and economic prosperity.